Effects of CrPic on performance and carcass characteristics in growing-finishing pigs - YU Dong-you; XU Zi-rong; CHEN Shi-jiang (浙江大学学报. 农业与生命科学版)
This study was conducted to investigate the effect of chromium picolinate on performance and carcass characteristics in growing-finishing pigs.144 pigs were randomly allotted to three treatments. There were 48 pigs in each treatment with three replicate pens of 16 pigs. The pigs were fed the diets supplemented with 0, 200, 400 μg·kg-1 chromium picolinate respectively. The results showed that chromium picolinate significantly decreased feed intake, feed gain ratio, fat percentage and 10th rib backfat thickness, increased average daily gain, dissected lean percentage, longissimus dorsi area, weight of longissimus muscle and biceps femoris compared with the control group. Futhermore, chromium picolinate increased the contents of protein fat, and RNA, RNA/DNA ratio in longissimus dorsi.